Does Political Reservation for Minorities Affect Child Labor? Evidence from India. (November 2016) - Kaletski, Elizabeth; Prakash, Nishith
Highlights: Explores the impact of minority political reservation on child labor in India. Scheduled Tribe reservation decreases the incidence of child labor. Much of the impact seems to occur within disadvantaged households. There are slight differences based on the gender of the child. Summary: This paper examines the impact of state-level political reservation for two minority groups–Scheduled Castes and Scheduled Tribes–on the incidence of child labor in India. We estimate the effect of political reservation on the incidence of child labor by exploiting the state variation in the share of seats reserved for the two minority groups in state legislative assemblies mandated by the Constitution of India. Using data from state and household-level surveys on fifteen major Indian states, we find that at the household level, Schedule Tribe reservation decreases the incidence of child labor, while Scheduled Caste reservation increases the total number of children working. We examine these impacts on the general as well as the disadvantaged group population independently, and across the gender of children. We also explore potential explanations for the differential impact of SC and ST political reservation, including geographic isolation, caste fragmentation, support for the Congress Party, and decentralization of power. Our results survive a variety of robustness checks.